2006
DOI: 10.1007/s00774-006-0727-7
|View full text |Cite
|
Sign up to set email alerts
|

Positive associations of bone mineral density with body mass index, physical activity, and blood triglyceride level in men over 70 years old: a TCVGHAGE study

Abstract: It is known that osteoporosis decreases physical function in older males. However, the role of metabolic parameters and physical activity influencing older men's bone status remains unclear. Thus, this study was designed to evaluate calcaneus bone mass by ultrasonic screening and the associated physical and metabolic functions in older men. This was a cross-sectional study. Three hundred sixty-eight older men (average age, 78.8 years) living in a veterans' home were enrolled. We measured body height and weight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 34 publications
1
21
0
Order By: Relevance
“…Conversely, other studies have shown positive associations between BMD of various skeletal sites and lower extremity PP measures [41, 77, 78]. Results of the study in 368 older men aged 78.8 ± 4.1 years living in a veterans' home in Taiwan [78] found that the calcaneus bone mass measured by Soundscan (quantitative ultrasound) expressed as broadband ultrasound attenuation was positively correlated with walking speed measured by a 6-minute walking distance.…”
Section: Resultsmentioning
confidence: 96%
“…Conversely, other studies have shown positive associations between BMD of various skeletal sites and lower extremity PP measures [41, 77, 78]. Results of the study in 368 older men aged 78.8 ± 4.1 years living in a veterans' home in Taiwan [78] found that the calcaneus bone mass measured by Soundscan (quantitative ultrasound) expressed as broadband ultrasound attenuation was positively correlated with walking speed measured by a 6-minute walking distance.…”
Section: Resultsmentioning
confidence: 96%
“…Although relevant data about the relationship between osteocalcin and lipid profile are scanty, there is increasing evidence showing a connection between lipids and bone metabolism in recent years. A number of studies focusing on the association between lipid profile and bone mass density (BMD) suggested that TG was positively associated with BMD and inversely associated with the presence of vertebral fractures (22)(23)(24). Adami et al also found reduced bone mass to be associated with a favorable lipid profile in healthy men (25).…”
Section: Discussionmentioning
confidence: 99%
“…(36)(37)(38) Unlike our data, TG level correlated positively with hip BMD and broadband ultrasound attenuation, whereas HDL-cholesterol level was correlated negatively with hip BMD in men. (39)(40)(41) There are other possible causes of low BMD in men with MetS. Men with MetS have lower levels of testosterone.…”
Section: Discussionmentioning
confidence: 99%